Pemanfaatan Complementary and Alternative Medicine pada ibu hamil - Agustini, Ni Komang Tri; Sagitarini, Putu Noviana; Anggaraeni, Komang Rosa Tri (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2023)
The use of CAM (Complementary and Alternative Medicine) is an important part as an option to reduce discomfort experienced by pregnant women. The aims of study describe the use of CAM in pregnant women during pregnancy. The result of study the largest source of information on using CAM was obtained from family and closest friends (42.9%). The reasons for using CAM during pregnancy were because it was easy to obtain and cheap (40.8%). Indications for using CAM are treating complaints of coughs, colds, flu during pregnancy (39.8%). The use of CAM during pregnancy is of great interest to pregnant women. The benefits obtained during the use of CAM are one of the reasons mothers use CAM. CAM is used to treat sickness experienced by mothers during pregnancy. However, there is a need for further research on mother's perceptions of using CAM and collaboration between medical health services and alternative medicine is urgently needed so that they can work together to improve maternal welfare.